SISTEM HONORIFIK BAHASA SAMAWA DAN FAKTOR YANG MEMENGARUHI PEMAKAIANNYA - Nur Ifansyah; Rini Qurratul Aini (Universitas Ahmad Dahlan, 2018)
The research intents on describing and explaining the honorifics forms of Samawa language and their use effect factors. The conducted method is case study. Source of data is native speaker of Samawa language in Sumbawa by purposive sampling. Data collection is conducted by in-depth interview with the informants. Data is analysed by interactive model. Furthermore, research findings present that (1) honorific forms of Samawa language is classified by two, they are referent honorific (first person pronoun, second person pronoun, and third person pronoun) and hearer honorific (family relation, professional relation, title, marital status, and general greeting nominal); (2) factor that affects the honorific use of Samawa language contains of power (sex, age, position in the family, occupation, position in an institution, marital status, and education), distance (solidarity, familiarity, and affect), and formality (purpose and setting).